Comparative Cardiotonic Activity of Gymnema Sylvestre With Digoxin On Isolated Frog Heart - Dholi, Shravan Kumar; K, Prasanna laxmi.; V, Ashok.; B, Vidhyasree.; ., Naresh (Asian Journal of Pharmaceutical Research and Development, 2013)
Gymnema Sylvestre (GS) is commonly used herb in Ayurveda. Chewing the leaves actually deadens the sense of sweet tastes and also the bitterness of bitter substances .This property is believed to be due to a glycoside known as gymnemic acid. Gymnemic acid (a mixture of triterpene glucuronides, which was found in the leaves. Present study was carried out to determine the cardiotonic activity by using infusion of G.S with different dilutions & compared with cardiotonic activity of digoxin‐the life saving cardiotonic. The activity was tested by using iso lated frog heart assembly. The present preliminary studies confirm the better cardiotonic activity of Gymnema Sylvestre than digoxin. Further studies can confirm the reduced toxicity & this will be the advantage of G.S over digitalis. Thus, in future it will be interesting to isolate the active chemical constituents which are responsible for the cardiotonic activity.